Edukasi, Demonstrasi, dan Praktik Menyikat Gigi untuk Meningkatkan Keterampilan Pemeliharaan Kesehatan Gigi dan Mulut pada Anak Usia Sekolah Dasar di Yayasan AL-Kahfi Kota Cirebon: Improving Oral Health Care Skills among Elementary School Children through Oral Health Education, Toothbrushing Demonstration, and Hands-on Toothbrushing Practice at the Al-Kahfi Foundation, Cirebon - Agista Nadiya Laura; Lina Khasanah; Aulia Halliza Goeshticha; Akhmad Fatkhul Anam; Dwi Nurlaila Febriyanti (Poltekkes Kemenkes Yogyakarta, 2025)
Oral health problems remain a public health challenge among school-aged children, particularly those living in residential care settings where access to health education and supervised healthy behaviors is limited. Preliminary observations at the Al-Kahfi Foundation in Cirebon indicated that several children had not yet practiced proper toothbrushing techniques, potentially increasing their risk of oral health problems. This community service program aimed to improve children's initial understanding and basic skills in maintaining oral health through interactive education, toothbrushing demonstrations, and supervised practice. The program was conducted at the Al-Kahfi Foundation, Cirebon, in August 2025 and involved 30 children aged 6–12 years. The intervention consisted of oral health education using dental models (phantoms), demonstrations of proper toothbrushing techniques, guided toothbrushing practice, and evaluation through oral questioning and direct observation of participants' toothbrushing techniques. All participants completed the activity with a 100% attendance rate. Based on observations during the evaluation and practice sessions, most participants were able to explain the importance of oral hygiene, identify the appropriate timing for toothbrushing, and demonstrate proper toothbrushing techniques according to the instructions provided. The educational and demonstration activities provided benefits in supporting participants' initial understanding and basic skills related to oral health maintenance. This visual-kinesthetic educational approach has the potential to serve as a promotive and preventive oral health promotion model that can be replicated in orphanages and other child residential care institutions with similar characteristics. The foundation management is encouraged to integrate supervised daily toothbrushing into children's routines and collaborate with the local primary healthcare center for regular oral health education and monitoring.